MicroRNA in Solid Tumor and Hematological Diseases - Lovat, Francesca (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
MicroRNAs (miRNAs), which are a type of short non-coding RNA, are involved in number of processes, such as differentiation, development, inflammation, immune response, and cancer. miRNAs, which act as oncogenes or tumor suppressor genes, can control and regulate the translation and stability of target messenger RNA, contributing to cancer pathogenesis. Despite the progress that has been made in discovering the mechanisms of how miRNAs function in tumors, many questions and aspects of miRNA biology and processing still remain to be determined. This Special Issue, titled "MicroRNA in Solid Tumor and Hematological Diseases", provides a panorama of the existing knowledge gaps and potential uses of microRNAs to predict clinical outcome or response to therapies and provides evidence to explain their role as biomarkers to modulate the biological pathways that are critical for cancer development and progression. It includes eleven peer-reviewed papers that cover the role of microRNAs in different tumor types and their potential applications in diagnosis and clinical approaches.